The Effect of Edible Coating Containing Plant Extract on Inhibiting the Growth of Aflatoxin in Nuts - mehrnoosh shirdeli; Maryam Sadat Shahidi; Matthew Shirani; ameneh marzban; Fatemeh Yaghoubi (Shahid Sadoughi University of Medical Sciences, 2020)
There is no abstract.